1050 ULTRASOUND GUIDED CANNULATION OF FEMORAL ARTERY IN PATIENTS UNDERGOING TRANSCATHETER AORTIC VALVE REPLACEMENT. (15th December 2022) - Di Costanzo, Assunta; Sorrentino, Sabato; Panarello, Alessandra; Spinali, Martina; Bellantoni, Antonio; Boccuto, Fabiola; Mariani, Andrea; Manzo, Rachele; Molaro, Maddalena Immobile; Polimeni, Alberto; Spaccarotella, Carmen; Mongiardo, Annalisa; et al.
Abstract: Background: Vascular access complications are a significant source of morbidity and mortality after transcatheter aortic valve replacement (TAVR). Ultrasound-guided cannulation (UGC) of central veins or arteries is a widely used approach for patients undergoing invasive procedures. Whether UGC significantly decreases the risk of vascular access complications also for large-bore access procedures, such as TAVR, lacks evidence Objectives: in this study, we aimed to evaluate the benefits of routine use of UGC in patients undergoing TAVR. Methods: Data were retrospectively collected from two high-volume TAVR centers from September 2009 to March 2022. UGC was performed using a two-dimensional ultrasound short-axis views, while manual palpation, fluoroscopy, or contralateral angiography were used for the other patients. The odds ratio (OR) for vascular complications was calculated using a multivariate logistic regression model including as dependent variables all relevant baseline and procedural characteristics (forward stepwise selection process). Vascular complications were adjudicated according to the Valve Academic Research Consortium definitions 3. Results: Out of 874 patients included in the study, UGC access was performed in 177 subjects. Overall mean age was 80.2±5.8 years old, 60% of patients were females, 35.5% had diabetes, 61.4% had dyslipidemia, and 27.8% had chronic kidney disease, with a mean left ventricular ejection fraction of 52.7±9.7%. Looking at the procedural variables Euroscore II was 5.8±5.4, second and third valves generation have been used in 85% of the cases, while suture-based closure devices in 84% of subjects. After adjustment for clinical and procedural variables, routinely use of UGC was associated with a lower rate of total [Odds Ratio (OR): 0.38; 95% confidence interval (CI) 0.15% to 0.95%)] and major vascular complications [Odds Ratio (OR): 0.21; 95% confidence interval (CI) 0.05% to 0.75%)], while no differences were observed for minor vascular complications. Conclusions: Routinely use of UGC significantly decreases the risk of vascular complications in patients undergoing TAVR. However, a dedicated randomized clinical trial assessing the safety and efficacy of this approach is warranted to confirm our results in this high-risk population.